Pengembangan Modul Ikatan Kimia Berbasis Guided Discovery Learning untuk Kelas X SMA - Wely Pramunando; Yerimadesi Yerimadesi (Edukimia, 2019)
This research aim to develop a guided discovery learning based chemical bonding module for grade X SMA and determine the level of validity and practicality. The type of this research was Research and Development using Plomp model. Plomp model consist of three stages, 1) preliminary research; 2) prototyping stage and 3) assessment stage. The validity test of this module was done by two chemistry lecturers at FMIPA UNP, two chemistry teachers at SMAN 3 Padang Panjang and a chemistry teacher at SMAN 4 Pariaman. Practicality test was done by two chemistry teachers at SMAN 3 Padang Panjang and 27 students XI MIPA 1 of SMAN 3 Padang Panjang using. Validity instrument and practical questionnaires was analysed by Cohen Kappa (k) Formula. The results of the analysis of the validity with an average score of the kappa moment 0.91 which is very high category of validity. The results of practicality by teacher and students show that the average score in a row is 0.95 and 0.87 which is very high practicality category. The data obtained show that guided discovery learning based chemical bonding module for grade X SMA produced is valid and practice.